Structure-Guided Identification of Resistance Breaking Antimalarial N‑Myristoyltransferase Inhibitors. Issue 7 (18th July 2019) - Schlott, Anja C.; Mayclin, Stephen; Reers, Alexandra R.; Coburn-Flynn, Olivia; Bell, Andrew S.; Green, Judith; Knuepfer, Ellen; Charter, David; Bonnert, Roger; Campo, Brice; Burrows, Jeremy; Lyons-Abbott, Sally; et al.
Summary: The attachment of myristate to the N-terminal glycine of certain proteins is largely a co-translational modification catalyzed by N-myristoyltransferase (NMT), and involved in protein membrane-localization. Pathogen NMT is a validated therapeutic target in numerous infectious diseases including malaria. In Plasmodium falciparum, NMT substrates are important in essential processes including parasite gliding motility and host cell invasion. Here, we generated parasites resistant to a particular NMT inhibitor series and show that resistance in an in vitro parasite growth assay is mediated by a single amino acid substitution in the NMT substrate-binding pocket. The basis of resistance was validated and analyzed with a structure-guided approach using crystallography, in combination with enzyme activity, stability, and surface plasmon resonance assays, allowing identification of another inhibitor series unaffected by this substitution. We suggest that resistance studies incorporated early in the drug development process help selection of drug combinations to impede rapid evolution of parasite resistance. Graphical Abstract: Highlights: Discovery of a mutant offering resistance against P. falciparum NMT inhibitor IMP-1002 Structural basis of the mechanism of resistance revealed by X-ray crystallography Genetic and chemical validation of resistance using CRISPR-Cas9 and enzyme assays Crystal structures of PvNMT[G386E] with IMP-1002 versus DDD85646, overcoming resistance Abstract : Structural studies of N-myristoyltransferase (NMT) of the malaria parasite Plasmodium falciparum combined with inhibitors decipher how a point mutation in nmt leads to the development of resistance against an inhibitor series, and enables identification of an NMT inhibitor that can overcome this resistance phenotype.